2020
DOI: 10.1136/bmjopen-2020-037892
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of rural communities towards the use of technology for health purposes in New Zealand: a focus group study

Abstract: ObjectivesExamine attitudes to using online health and wellness services, and determine what barriers may exist to this in two rural communities in New Zealand.DesignA thematic analysis informed by a social constructivist paradigm explored the attitudes of youth and adults to give voice to these communities. Eighteen focus groups—nine in each region—were held for an hour each, with between three and nine participants in each group.SettingTwo rural areas at the Northern and Southern ends of New Zealand were cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Babbage et al . (2020) also examined attitudes towards using online health and well‐being services. Babbage et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Babbage et al . (2020) also examined attitudes towards using online health and well‐being services. Babbage et al .…”
Section: Resultsmentioning
confidence: 99%
“…Babbage et al . (2020) found that younger men and women were more likely to use digital technology than older participants. However, in some rural location’s, Internet access is poor and is a limiting factor in using online health activities as the expense to use satellite access is prohibitive.…”
Section: Resultsmentioning
confidence: 99%
“…The final results included a methodologically diverse dataset comprising 12 quantitative studies, six qualitative studies, eight mixed methods, 15 review articles and two book chapters. Despite our intentional search strategy, we located only one article from Aotearoa New Zealand (Babbage et al, 2020 ) and two articles from Australia (Dham et al, 2018 ; Simpson et al, 2015 ). This reflects the limited degree of contemporary evidence-based discourse in the context of the Global South, whilst the significant majority of articles reported on research conducted in the Global North.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of clients living in rural and remote areas (Dham et al, 2018 ), high patient satisfaction with online therapy was reported, and accessibility was identified as one of the most significant benefits for socially isolated individuals. Similarly, a survey of rural New Zealanders identified strong support for distanced mental healthcare amongst rural communities (Babbage et al, 2020 ). In contrast to these optimistic client perspectives, a study of attitudes towards telehealth care amongst rural mental health professionals identified a consistent degree of scepticism regarding the efficacy of telehealth care (McClellan et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation